Precision hole making on laminate composite: a tool wear analysis and comparison between drilling and punching. (2016) - Ghaffar, N.A.; Abdullah, A.B.; Samad, Z.
Hole precision is highly critical for accurate and strong fastener assembly. This factor is considerably important for structural materials, such as composite materials. Drilling is the most commonly used process for producing holes on composites. However, drilling causes excessive tool wear, which may affect the quality of holes and result in damage, such as delamination. The main objective of this study is to compare the drilling and punching processes in terms of tool wear by using the focus variation technique. The scanned images of both the puncher and drill bits are obtained by using a 3D optical surface measurement device called Alicona IFM. Tool wear patterns from both drilling and punching are analysed and compared, and the effects of the processes on the quality of the produced holes are observed.